Body composition, cardiorespiratory fitness, and neuromuscular adaptations induced by a home-based whole-body high intensity interval training - Corentin Scoubeau; Julie Carpentier; Stéphane Baudry; Vitalie Faoro; Malgorzata Klass (Elsevier, 2023)
Background/objective: Bodyweight exercises performed at home could be a complementary approach to improve health-related fitness in people having little spare time and during stay-at-home periods. This study then investigated body composition, cardiorespiratory fitness, and neuromuscular adaptations to a home-based, video-directed, whole-body high-intensity interval training (WB-HIIT). Methods: Fourteen subjects participated to an 8-week WB-HIIT (6 females, 23 ± 1 years) and fourteen were included in a non-exercise control group (CTL; 6 females, 24 ± 4 years). All took part to pre- and post-intervention assessments of body composition, peak oxygen uptake (VO2peak) and first ventilatory threshold (VT1; index of aerobic capacity), dynamic (leg press 3-repetition maximum) and isometric strength (knee extensors maximal isometric contractions with assessment of voluntary activation), and muscle endurance during an isometric submaximal contraction maintained till exhaustion. WB-HIIT consisted in 30-s all-out whole-body exercises interspaced with 30 s of active recovery. Training sessions were performed at home by means of videos with demonstration of exercises. Heart rate was monitored during sessions. Results: WB-HIIT increased VO2peak (5%), VT1 (20%), leg lean mass (3%), dynamic (13%) and isometric strength (6%), and muscle endurance (28%; p < 0.05), while they did not improve in CTL. VO2peak increase was correlated (r = 0.56; p < 0.05) with the time spent above 80% of maximal heart rate during training sessions. Isometric strength increase was correlated with change in voluntary activation (r = 0.74; p < 0.01). Conclusion: The home-based WB-HIIT induced concomitant cardiorespiratory fitness and neuromuscular improvements. The predominant effect was observed for aerobic capacity and muscle endurance which could improve exercise tolerance and reduce fatigability.